The clinical features of chronic intestinal schistosomiasis-related intestinal lesions - Qin, Xian (BMC Gastroenterol, 2021)
BACKGROUND: Chronic intestinal schistosomiasis has been reported to be associated with colonic polyps, colorectal cancer and ulcerative colitis. We aim to investigate the clinical characteristics of intestinal-related lesions caused by chronic intestinal schistosomiasis japonicum. METHODS: Patients with and without chronic intestinal schistosomiasis were retrospectively enrolled from the endoscopy center of Wuhan Union Hospital from September 1, 2014, to June 30, 2019 with a ratio of 4:1. The characteristics of infected intestinal segments were analyzed in patients with chronic intestinal schistosomiasis. We also compared the characteristics of intestinal-related lesions, including colorectal polyps, colorectal cancer (CRC), ulceration or erosion of the intestinal mucosa and hemorrhoids, between the two groups. RESULTS: A total of 248 patients with chronic intestinal schistosomiasis and 992 patients without chronic intestinal schistosomiasis were analyzed. The most common sites of chronic intestinal schistosomiasis were the sigmoid colon (79.0%) and rectum (84.7%). The frequency of intestinal polyps (64.5% vs. 42.8%, p < 0.001), especially rectal polyps (62.5% vs. 45.0%, p = 0.002), in the intestinal schistosomiasis group was significantly higher than that in the control group. Morphologically, type IIa polyps were more common in the schistosomiasis enteropathy group (68.5% vs. 60.7%, p = 0.001). Female patients with intestinal schistosomiasis had a higher detection rate of CRC than women in the control group (13.8% vs. 5.4%, p = 0.017). There was no significant difference in the incidence of ulcerative colitis between the two groups (0.8% vs. 0.6%, p = 0.664). In addition, the schistosomiasis enteropathy patients had a higher detection rate of internal hemorrhoids (58.9% vs. 51.0%, p = 0.027). CONCLUSIONS: Chronic intestinal schistosomiasis mainly involved the rectum and sigmoid colon and was more likely to induce intestinal polyps, especially rectal polyps and internal hemorrhoids. Women with chronic schistosomiasis have a higher risk of colorectal cancer.